Influences of ecology and climate on the distribution of restricted, rupicolous reptiles in a biodiverse hotspot. Issue 2 (13th December 2019) - Petford, MA; van Huyssteen, R; Alexander, GJ
ABSTRACT: Understanding the role of climatic and ecological factors in limiting species to their distributions is becoming ever more important in a world where anthropogenic activities are increasingly threatening species persistence. Species with restricted distributions are often poorly known even though they may be most vulnerable to extinction. We investigated the influences of climate and ecology on the distribution of five understudied, endemic, rupicolous reptiles from the Soutpansberg Mountains in South Africa. Using Maxent, we developed ecological niche models that were used to provide baseline insights into the factors delimiting these species distributions. Results indicated that most species were limited by climatic factors, with the average temperature of the coolest quarter having the most influence on the majority of the species, where they were limited to areas with cooler temperatures. This suggests that they may be negatively affected by climate change in the future. Distribution maps revealed that there were no strong interspecific interactions influencing the distributions between the species investigated and identified potential new localities for two species. There was high endemic richness located in the western Soutpansberg and this is likely to have been driven by past climatic and erosion events. Overall this study highlighted that performing environmental niche models on understudied species can provide essential, baseline information on which to drive future research.